Messages from Ukraine - Bucken-Knapp, Gregg (ethnoGRAPHIC (University of Toronto Press), 2022)
"Two days after the wide-scale Russian invasion of Ukraine took place on February 24, 2022, Gregg Bucken-Knapp sent text messages offering help to Ukrainian migration and integration professionals. He found himself filling in the visual gaps as he read their text messages--trying to imagine their immediate circumstances as they chose to stay and volunteer or fight, or sought safety elsewhere. In graphic form, Messages from Ukraine explores the varied experiences of the people who sent these messages: those who were forced to flee home and seek safety elsewhere in Ukraine or abroad, those who remained to take part in war efforts, those who were abroad at the time and witnessed the unfolding of events from afar, and those who found themselves trapped in Ukrainian cities under siege. The book includes a study guide with questions and activities for students as well as a timeline to assist with contextualizing events. Through the use of images that frame and interpret messages from the perspective of the recipient, Messages from Ukraine proves that comics can shed meaningful light on war, displacement, and resilience."--